Ferulic acid regulates the Nrf2/heme oxygenase-1 system and counteracts trimethyltin-induced neuronal damage in the human neuroblastoma cell line SH-SY5Y. - Stefania eCatino; Fabiola ePaciello; Fiorella eMiceli; Rolando eRolesi; Diana eTroiani; Vittorio eCalabrese; Rosaria eSantangelo; Cesare eMancuso (Frontiers Media S.A., 2016)
Over the past years, several lines of evidence have pointed out the efficacy of ferulic acid (FA) in counteracting oxidative stress elicited by β-amyloid or free radical initiators, based on the ability of this natural antioxidant to up-regulate the heme oxygenase-1 (HO-1) and biliverdin reductase (BVR) system. However, scarce results can be found in literature regarding the cytoprotective effects of FA in case of damage caused by neurotoxicants. The aim of this work is to investigate the mechanisms through which FA exerts neuroprotection in SH-SY5Y neuroblastoma cells exposed to the neurotoxin trimethyltin. Ferulic acid (1-10 μM for 6 h) dose-dependently increased both basal and TMT (10 μM for 24 h)-induced HO-1 expression in SH-SY5Y cells by fostering the nuclear translocation of the transcriptional activator Nrf2. In particular, the co-treatment of FA (10 μM) with TMT was also responsible for the nuclear translocation of HO-1 in an attempt to further increase cell stress response in SH-SY5Y cells. In addition to HO-1, FA (1-10 μM for 6 h) dose-dependently increased the basal expression of BVR. The antioxidant and neuroprotective features of FA, through the increase of HO activity, were supported by the evidence that FA inhibited TMT (10 μM)-induced lipid peroxidation (evaluated by detecting 4-hydroxy-nonenal) and DNA fragmentation in SH-SY5Y cells and that this antioxidant effect was reversed by the HO inhibitor Zinc-protoporphyrin-IX (5 μM). Among the by-products of the HO/BVR system, carbon monoxide (CORM-2, 50 nM) and bilirubin (50 nM) significantly inhibited TMT-induced superoxide anion formation in SH-SY5Y cells. All together, these results corroborate the neuroprotective effect of FA through the up-regulation of the HO-1/BVR system, via carbon monoxide and bilirubin formation, and provide the first evidence on the role of HO-1/Nrf2 axis in FA-related enhancement of cell stress response in human neurons.